(untitled) (Studia Prawnicze / The Legal Studies, 1985)
At present in some countries (not in Poland) a concept of a new branch of law has emerged, i.e. social law. Its scope has not been specified yet and its separation from other branches of law has not been justified yet. In some formulations of the concept the borderline between law and the sphere of social policy is not clear, which is undesired. Law constitutes an im,portant but only one of many means of realization of the policy. Modern labour law emerged from protective labour legislation according to the postulates of social, policy. However, labour law as a branch of science and subject taught at universities was formed only after the Second World War and its origins go back to the interwar period. It emerged many years after first laws on the protection of labour were adopted. The analysis of the situation in Poland, USSR, France, Belgium, Federal Republic of Germany, Great Britain and USA reveals that the scope of labour law is different in those countries and that a new branch of law has been being formed, i.e. law of social protection. In some countries the object of law of social insurance is wider and is called law of social protection. The concept of social law is connected with the idea of social protection. It is the next stage of development of law. The notion of social law is a collective notion. It may embrace various branches of law, especially labour law, law of social insurance (or social protection) law of health protection, housing law. However, at the present stage of development of law and separation of the branch of science of law only labour law and social insurance law may be referred to as social law. Nevertheless, a further development of the concept of social law may be expected.